Strategies for Developing Harmonious (Sakinah) Families at the Office of Religious Affairs - Ananda, Firza Yulia; Nurhanifah, Nurhanifah (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This research aims to analyze the strategy of developing a sakinah family in the Office of Religious Affairs of Medan Tembung Subdistrict and identify the implementation of POACE-based da'wah management principles (Planning, Organizing, Actuating, Controlling, Evaluating) in the implementation of the program. This research used a descriptive qualitative approach with data collection techniques through observation, in-depth interviews, and documentation. The main informants consisted of the Head of the KUA, Functional Islamic Religious Instructor (PAIF), and two community members. Secondary data were obtained from relevant literature. Data validity was tested through triangulation of sources and techniques. Data analysis used Miles and Huberman's interactive model which includes data reduction, data presentation, and conclusion drawing. The results showed that the strategy of developing a sakinah family in the KUA of Medan Tembung Subdistrict is carried out through a combination of national programs from the Ministry of Religious Affairs such as Bimwin, BRUS, and BRUN, as well as an internal approach that emphasizes the value of worship, sharia legal consultation, and sustainable family assistance. The implementation of this strategy is managed with the principles of POACE (Planning, Organizing, Actuating, Controlling, Evaluating) da'wah management which proved to be effective, as seen from the low number of post-marriage complaints and the high appreciation of the community for the program which is considered to touch various important aspects of household life.